Parenting Styles and Emotional Intelligence: A Cultural Study on Secondary School Students in China - Jabbar, Muhammad Naveed; Deli, Wu; Shehzad, Muhammad Waleed (International Journal of Psychosocial Rehabilitation, 2020)
Parenting styles are psychological constructs representing standard strategies that parents use in their child rearing and emotional intelligence helps the students to act positively for the enhancement of their academic achievements. The main objective of this paper is to investigate the effect of parenting styles on students’ emotional intelligence. The study is based on the quantitative cross sectional research design. The secondary school students from China were the population of this study whereas, 213 respondents were selected as sample through simple random technique. The data was collected through standardize questionnaire by using survey method. SPSS Ver.25 was administered for descriptive and inferential statistics. The findings of the study revealed that there was a moderate and positive effect of parenting styles on emotional intelligence of the secondary school students. Moreover, Authoritative and permissive styles of parenting have strong positive effect on emotional intelligence than authoritarian. This study is beneficiary for parents and educationists that they have keep in mind the importance of emotional intelligence of students during the curricular and extracurricular activities.